2015
DOI: 10.1186/s12889-015-2402-1
|View full text |Cite
|
Sign up to set email alerts
|

Active smoking and exposure to secondhand smoke and their relationship to depressive symptoms in the Korea national health and nutrition examination survey (KNHANES)

Abstract: BackgroundThe relationship between tobacco smoking, including secondhand smoking, and depression has been assessed. The purpose of this study was to evaluate the association between secondhand smoking among current, former and never smokers and depressive symptoms. For secondhand smoking, gender differences and sources of exposure were examined.MethodsData from 34,693 participants from the fourth and fifth Korean Health and Nutritional Examination Survey (2007–2012) were analyzed in 2014. Self-reported exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 51 publications
4
34
1
Order By: Relevance
“…Reviewing intervention researches, Meer et al concluded that the control of humor combined with standard treatments is an important component to increase the percentage of cessation success 22 . The association of passive smoking at home with presence of depression, identified in this study, has also been found by Jung et al 23 for the female population in a study held in Korea.…”
Section: Discussionsupporting
confidence: 89%
“…Reviewing intervention researches, Meer et al concluded that the control of humor combined with standard treatments is an important component to increase the percentage of cessation success 22 . The association of passive smoking at home with presence of depression, identified in this study, has also been found by Jung et al 23 for the female population in a study held in Korea.…”
Section: Discussionsupporting
confidence: 89%
“…Since life satisfaction is robustly associated with mental health problems [10], our finding is in agreement with prior studies that have examined the impact of SHS on mental health [79]. One possible biological explanation for this finding could be that SHS exposure is linked with low-grade inflammation which is strongly associated with mental health problems, particularly mood disorders like depression [15].…”
Section: Discussionsupporting
confidence: 90%
“…These results are similar to the findings from previous research that secondhand smoke may increase the risk of depressive symptoms. 3 4) However, the unique finding of this study is that secondhand smoke may be associated with suicidal ideas.…”
mentioning
confidence: 71%